Speculative everythig : design, fiction, and social dreaming - Dunne, Anthony, ....-; Raby, Fiona, ....- (Cambridge, Massachusetts, London : The MIT Press, 2013)
In Speculative Everything Dunne and Raby continue to inspire and challenge us to consider design as a unique mode of sociocultural inquiry. Rather than resigning design to either problem solving or styling, what Dunne and Raby offer is a vibrant practice of using design to materialize and experiment with alternate worldviews and futures. Speculative Everything is an important contribution to the field of design and should be read widely. Carl DiSalvo ,author of Adversarial Design In a period where existing systems are reaching their effective limits, Speculative Everything describes an expanded and refreshing role for design. Dunne and Raby show how speculative design can stimulate debate and reveal choices that exist beyond the constraints of existing business, social, and technological approaches. Tim Brown ,CEO, IDEO Anthony Dunne and Fiona Raby have set out to change the landscape of contemporary design. They remind us that design is about asking questions, as well as answering them. Speculative Everything, their provocative manifesto, is an intriguing contribution to the search for a new direction for design. Deyan Sudjic ,Director, Design Museum, London
Keywords: Design